Self-assessed Confidence of Dentists in Pediatric Dentistry: A cross-sectional study - Babar, Palwasha; Haider, Irsam (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the confidence of dentists in provision of dental treatment for children and to explore the status of the current pediatric dental services offered by the dental practitioners. Methodology: A self-structured questionnaire was administered. Data was collected from both academic and non-academic dental practitioners and specialists. Pediatric dentists were excluded from the study. Results: The results show that there is lack of undergraduate training in the subject of pediatric dentistry. Dentists reported low confidence in various pediatric dental procedures. The provision of dental services to the pediatric patients was also observed to be inadequate. Conclusion: The undergraduate education of pediatric dentistry is of paramount importance. The curriculum should be structured in such a way so that it translates into provision of best dental services to the children. There is need for continuing education courses for dentists in pediatric dentistry in order to ensure adequate dental care for children.